Tuesday

July 22, 2014

July 22, 2014

Posted by **Muiz** on Friday, January 11, 2013 at 12:49am.

- math -
**Reiny**, Friday, January 11, 2013 at 8:02amI will assume:

2x^-1 - 3y^-1 = 4 ---> 2/x - 3/y = 4

and

4x^-1 + y^-1 = 1 ----> 4/x + 1/y = 1

double the first : 4/x - 6/y = 8

keep the 2nd : 4/x + 1/y = 1

subtract them:

-7/y = 7

7y = -7

y = -1

back into the 2nd:

4/x + 1/-1 = 1

4/x = 2

2x = 4

x = 2

**Related Questions**

Pre-Algebra - If negative 20 equals 168, negative 15 equals 153, negative 10 ...

algebra - Could someone show me how to solve this joint variation problems? Y ...

algebra ll - solve the system of equation. 4x - 3y equals 14 y equals -3x plus 4...

math - write the equation 5x plus y equals 2 which equals 0 in normal form. my ...

Pre-Algebra - If negative 20 equals 168, negative 15 equals 153, negative 10 ...

Math - Rectangles ABCD and EFGH are similar figures because angles A, B, C, and ...

Math - 1. 24 quarts equals 6 gallons? 2. 5 cups equals 40 quarts? 3. 8 cups ...

geometry - Construct trapezium ABCD so that BC equals 6cm,AB equals 3cm,Angle B ...

math/algebrall - solve the system of equations:4x - 3y equals 14 and y equals -...

math - 1/4x-1/6y=-2 -1/6x+1/5y=4 solve for x and y its suppose to be x equals 12...